Analysis of Defuzzification Method for Rainfall Event - Uraon, Kiran Kumar; Kumar, Shiv (IJRDO -Journal of Computer Science Engineering, 2016)
Fuzzy Logic is present trend for decision making, classification and prediction where problem can be formulated by mapping input variable with output variable or where simple solution does not exists. There are three basic steps for fuzzy inference system such as Fuzzification, rule evaluation and Defuzzification. Fuzzification means converting numeric value into linguistic value. Human intuition method is well accepted method for the membership function value assignment throughout the world. Fuzzy inference engine produce the result after rule evaluation also in terms of linguistic value. All results are aggregated and defuzzified by any Defuzzification method. It is very difficult to know which process will be suitable for which type of data. So, the main objective of this paper is to explore the basic concept of Defuzzification method for the rain fall event with the help of wind speed and temperature variable by simulating on matlab analyze the obtained results for different-different fuzzyfication methods the rain fall event in “MatLab”.